Metabolic responses to Orientia tsutsugamushi infection in a mouse model. - Jeeyoun Jung; Youngae Jung; Byoungchul Gill; Changhun Kim; Kyu-Jam Hwang; Young-Ran Ju; Hye-Ja Lee; Hyuk Chu; Geum-Sook Hwang (Public Library of Science (PLoS), 2015)
Tsutsugamushi disease is an infectious disease transmitted to humans through the bite of the Orientia tsutsugamushi-infected chigger mite; however, host-pathogen interactions and the precise mechanisms of damage in O. tsutsugamushi infections have not been fully elucidated. Here, we analyzed the global metabolic effects of O. tsutsugamushi infection on the host using 1H-NMR and UPLC-Q-TOF mass spectroscopy coupled with multivariate statistical analysis. In addition, the effect of O. tsutsugamushi infection on metabolite concentrations over time was analyzed by two-way ANOVAs. Orthogonal partial least squares-discriminant analysis (OPLS-DA) showed distinct metabolic patterns between control and O. tsutsugamushi-infected mice in liver, spleen, and serum samples. O. tsutsugamushi infection caused decreased energy production and deficiencies in both remethylation sources and glutathione. In addition, O. tsutsugamushi infection accelerated uncommon energy production pathways (i.e., excess fatty acid and protein oxidation) in host body. Infection resulted in an enlarged spleen with distinct phospholipid and amino acid characteristics. This study suggests that metabolite profiling of multiple organ tissues and serum could provide insight into global metabolic changes and mechanisms of pathology in O. tsutsugamushi-infected hosts.